Crossing the Farak River - Aung Thin, Michelle (Annick Press, 2020)
Hasina is part of the Rohingyas people in Rakhine province of Myanmar. She, like all her fellow Rohingyas, know to run when the helicopters of the Sit Tat--the oppressive Myanmar Army--come thundering overhead. One night they do just that, and Hasina must flee with her brother, Araf, and her cousin Ghadiya. Days later, they return to find all their family and fellow Rohingyas gone, and the three must find a way to live in this new conflict.